Bankruptcy of an individual in Russia: state and prospects of development - Evenko V.V., V. Yu. Soldatenkov (Opción, 1970)
The aim of the study is to identify the areas of improving the bankruptcy institution of individuals in Russia. In this study, methods of observation, generalization, deduction, comparative and system analysis were applied. As a result, the authors consider that the institution of insolvency (bankruptcy) of a debtor in Russia should be improved taking into account the following principles: 1) Bankruptcy proceedings should be applied to the debtor in order to fulfill monetary obligations towards creditors, not for writing off debts; 2) Bankruptcy proceedings for conscientious citizens-debtors should be simplified; 3) Possibilities of abuse in bankruptcy cases should be excluded.